Spray form Solarsept vs. diluted sodium hypochlorite for the disinfection of alginate impressions - Katalbas, Fidel Jacob I.
INTRODUCTION: Alginate is an impression material that is prone to dimensional changes; therefore it is recommended to pour the stone as soon as possible when using this material. Unsurprisingly, due to time constraint, disinfection of this material could frequently be overlooked and rinsing the impression under running water is all that is done. Spray disinfection is a convenient disinfection method that requires minimal time and effort to perform, thus the objective of this study is to determine the effectiveness of two sprayed disinfectants, spray form Solarsept and diluted sodium hypochlorite (1:10), in reducing microbial load of alginate impressions under the time when alginate supposedly changes in dimension.